Nicotinamide reduces renal interstitial fibrosis by suppressing tubular injury and inflammation. Issue 6 (16th April 2019) - Zheng, Meiling; Cai, Juan; Liu, Zhiwen; Shu, Shaoqun; Wang, Ying; Tang, Chengyuan; Dong, Zheng
Abstract: Renal interstitial fibrosis is a common pathological feature in progressive kidney diseases currently lacking effective treatment. Nicotinamide (NAM), a member of water‐soluble vitamin B family, was recently suggested to have a therapeutic potential for acute kidney injury (AKI) in mice and humans. The effect of NAM on chronic kidney pathologies, including renal fibrosis, is unknown. Here we have tested the effects of NAM on renal interstitial fibrosis using in vivo and in vitro models. In vivo, unilateral urethral obstruction (UUO) induced renal interstitial fibrosis as indicated Masson trichrome staining and expression of pro‐fibrotic proteins, which was inhibited by NAM. In UUO, NAM suppressed tubular atrophy and apoptosis. In addition, NAM suppressed UUO‐associated T cell and macrophage infiltration and induction of pro‐inflammatory cytokines, such as TNF‐α and IL‐1β. In cultured mouse proximal tubule cells, NAM blocked TGF–β‐induced expression of fibrotic proteins, while it marginally suppressed the morphological changes induced by TGF‐β. NAM also suppressed the expression of pro‐inflammatory cytokines (eg MCP‐1 and IL‐1β) during TGF‐β treatment of these cells. Collectively, the results demonstrate an anti‐fibrotic effect of NAM in kidneys, which may involve the suppression of tubular injury and inflammation.